Dental fear prevalence among the adult residents of Brgy. Cambaog, Bustos, Bulacan - Cheung, Brenda T.
The presence of dental anxiety among patients is a well recognized problem in many countries. It is one of the reasons why patients avoid dental visits and fail to receive appropriate dental care. However, the prevalence of dental fear among Filipinos has not been well-documented. This sudy aims to detemine the prevalence and demographic profile of the adult residents of Brgy. Cambaog, Bustos, Bulacan with dental fear. Methods: 338 randomly selected adult residents completed a two part questionnaire. The first part included questions regarding personal information, dental visits and self-assessed oral health status while the second part is Corah's Dental Anxiety Scale translated in Filipino which will measure dental anxiety. Results: It was revealed that 11% of the subjects are dentally anxious after having DAS scores ≥ 13. Their mean age was 35 year old. 47% of hem had their last dental visit more than a year ago and 84% have fair to poor self-assessed oral health status. 14% of the female subjects and 7% of the male subjects are dentally anxious. 37% of the subjects reported avoidance of dental visits due to dental fear, the most common reasons of which were tooth extraction, needle injection and pain. Conclusion: Dental anxiety concerns a significant proportion of adult residents of Brgy. Cambaog. It must be recognized and addressed by dentists by thorough patient assessment and development of appropriate management procedures. This will not only enhance delivery of optimum oral care but also improve the patient-doctor relationship.